Use of DNA capture kits to collect Xanthomonas campestris pv. musacearum and banana bunchy top virus pathogen DNA for molecular diagnostics - Ramathani, I.; Beed, Fenton D. (CAB International, 2013)
Banana Xanthomonas wilt, caused by the bacterium Xanthomonas campestris pv. musacearum, and banana bunchy top virus disease (BBTD), caused by the banana bunchy top virus (BBTV), are two of the most devastating diseases of banana in East and Central Africa, and cause significant losses in food security and income for millions of farmers, traders and consumers. To prevent the establishment and spread of the diseases across the region, control interventions must be rapidly deployed. A first and critical step towards deployment of appropriate disease management strategies is the rapid and precise diagnosis of the causal agent of disease. The diagnosis of Xanthomonas wilt in the field based on disease symptoms is often confused with another disease that causes wilting that is due to the fungus Fusarium oxysporum f.sp. cubense, so diagnostic tools that are easy to use, cost-effective and reliable are required to help field workers. BBTD symptoms can also be confused with nutrient deficiencies or varietal differences. To this end, three types of portable kits were evaluated for their performance in capturing pathogen DNA from the field for use in precise, molecular-based pathogen diagnostics under controlled laboratory conditions. All three prototypes tested – FTA cards, the PhytoPASS kit and two-minute DNA extraction dipsticks – gave excellent results and methods were optimized for sample collection in the field, DNA extraction and PCRbased diagnostics for X. campestris pv. musacearum and BBTV. The benefits of using DNA capture kits included: collection of pathogen DNA in a cheap and practical manner, safe and fast transfer of high integrity pathogen DNA across country borders, rapid and precise diagnosis using state-of-the-art molecular technologies and direct comparison of results from geographically diverse samples. This is possible because analysis is performed in a uniform manner in terms of method, date, equipment, reagents and technical staff. Technical support was provided to workers in the field to help them differentiate symptoms based on diagnostic results from laboratory analyses; such support could also be provided to regulatory officials at borders to ensure that, for example, planting material is free from disease. Countries involved in testing the DNA capture kits for X. campestris pv. musacearum included Burundi, Democratic Republic of Congo (DR Congo), Kenya, Rwanda, Tanzania and Uganda. The same countries, with Zambia also included, were also tested for BBTV. While no positive results for X. campestris pv. musacearum were obtained from samples originating from surveys in Burundi, subsequent DNA capture kits from samples from Bubanza and Cankuzo provinces did test positive, thus confirming an outbreak of Xanthomonas wilt in this country. BBTV was confirmed in DR Congo, Burundi, Rwanda and Zambia.